Advances in mobile computing and communications perspectives and emerging trends in 5G networks - Krishna, M. Bala; Lloret Mauri, Jaime (CRC Press, 2016)
By 2020, if not before, mobile computing and wireless systems are expected to enter the fifth generation (5G), which promises evolutionary if not revolutionary services. What those advanced services will look like, sound like, and feel like is the theme of the book Advances in Mobile Computing and Communications: Perspectives and Emerging Trends in 5G Networks. The book explores futuristic and compelling ideas in latest developments of communication and networking aspects of 5G. As such, it serves as an excellent guide for advanced developers, communication network scientists, researchers, academicians, and graduate students. The authors address computing models, communication architecture, and protocols based on 3G, LTE, LTE-A, 4G, and beyond. Topics include advances in 4G, radio propagation and channel modeling aspects of 4G networks, limited feedback for 4G, and game theory application for power control and subcarrier allocation in OFDMA cellular networks. Additionally, the book covers millimeter-wave technology for 5G networks, multicellular heterogeneous networks, and energy-efficient mobile wireless network operations for 4G and beyond using HetNets. Finally, the authors delve into opportunistic multiconnect networks with P2P WiFi and cellular providers and video streaming over wireless channels for 4G and beyond.
Includes bibliographical references and index. - Print version record
Keywords: Mobile computing; Mobile communication systems; Informatique mobile; Radiocommunications mobiles